An econometric model of the Greek economy - Suits, Daniel Burbidge (Athens, Greece : Center of Economic Research, 1964)
In this book the author attempts to construct a full-scale econometric model for a less developed economy. The model presented in this volume, despite the unavoidable limitations of data, gives substantial empirical insight into the structure of the Greek economy and undoubtedly will be useful in making predictions for the purposes of policy formulation.
Includes bibliographical footnotes.
rpm 28/11/2017
Loans
Keywords: Economics; Greece